Relation between saturated and normal operators - Sah, Nagendra Pd (BIBECHANA, 2013)
A vector space X with algebra of all linear maps ∑(X) from X into itself and the ideal of all finite dimensional linear maps with dual (Conjugate) transformation T* to T from X' to itself form a relation in terms of relatively regular and linearly independent which is sufficient for mentioned title. DOI: http://dx.doi.org/10.3126/bibechana.v10i0.9342 BIBECHANA 10 (2014) 115-117